2014
DOI: 10.9790/0837-19240107
|View full text |Cite
|
Sign up to set email alerts
|

Parental Acceptance, Mental Health and Self-efficacy of Adults in Bangladesh

Abstract: The present study explored the relation of remembered parental (paternal and maternal) acceptance in childhood with mental health and self-efficacy of adults in Bangladesh. The sample consisted of 150 adults (50% women) ages 18 through 25 years (M = 22.01years) from Bangladesh. The measures used Results of the correlation analyses indicated that remembered maternal and paternal acceptances were significantly correlated with adults' mental health and self-efficacy. Results of multiple regression analyses reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
2
0
4
Order By: Relevance
“…So, both male and female perceived loved and accepted by their parents. The present result also supported by the existing literature (Aktar and Nahar, 2014) showed that both men and women perceived their mothers as well as fathers to be fairly accepted. No significant gender difference was found in perceived maternal and paternal acceptance.…”
Section: Discussionsupporting
confidence: 90%
“…So, both male and female perceived loved and accepted by their parents. The present result also supported by the existing literature (Aktar and Nahar, 2014) showed that both men and women perceived their mothers as well as fathers to be fairly accepted. No significant gender difference was found in perceived maternal and paternal acceptance.…”
Section: Discussionsupporting
confidence: 90%
“…al., 2016) ukazuje na značajnu povezanost između podrške roditelja i samoefikasnosti pri donošenju karijernih odluka. Interesantan nalaz dobijen je u istraživanju koje je sprovedeno na uzorku starijih adolescenata (Aktar & Nahar, 2014). Naime, rezultati regresione analize pokazali su da je doživljaj prihvatanja od majke jači prediktor mentalnog zdravlja nego doživljaj prihvatanja od oca, dok je, u slučaju samoefikasnosti, doprinos očinskog prihvatanja značajniji od doprinosa majčinog prihvatanja.…”
Section: Uloga Roditelja U Razvoju Samoefikasnostiunclassified
“…Veneziano, 2000; Kim et al, 2006;Aktar and Nahar, 2014). Accepted children, in general, tend to have less psychological maladjustment problems (Glavak-Tkalić and Kukolja-Cicmanović, 2014).…”
Section: Problem Statementmentioning
confidence: 99%